Performance of PSA and of PSA density in the diagnosis of prostate carcinoma - Martins,Antonio Carlos Pereira (2002)
OBJECTIVE: The aim of the study was to investigate the influence of the prostate volume and PSA density on the performance of total PSA to diagnosis of prostate carcinoma. METHODS: We analyzed 217 patients (PSA 0-10ng/ml) submitted to transrectal sextant prostate biopsy. Criteria for biopsy indication was PSA >2ng/ml and/or digital rectal exam suspicious of prostate cancer. RESULTS: Fifty five patients had prostate neoplasia (25.3%) and in 8/55 (25.3%) the serum PSA was under 4ng/ml. The sensitivity and specificity of the test were respectively 98.2% / 16.6% at a cut-off point of 2.5ng/ml and 85.4% / 38.8% at cut-off of 4ng/ml. The corresponding values for prostates >40ml or <40ml were: 96.2% / 8.1% and 100% / 27.2% at the cut-off point of 2.5ng/ml, and 92.5% / 20% and 78.5% / 62.3% at a cut-off level of 4ng/ml. For prostates <40ml a PSA cut-off point of 4ng/ml leads to a misdiagnosis in 21.4% of the malignant tumors. The median PSAD of benign prostates are different according to prostate volume (.40ml or <40ml). PSAD at cut-off of 0.08 increases the PSA specificity at both PSA cut-off points. CONCLUSIONS: Prostate volume affects the sensitivity and specificity of PSA and the median values of PSAD. PSAD of 0.08 increases the PSA specificity specially at a cut-off point of 2.5ng/ml in prostates smaller than 40ml.